Distinct Profiles of CD163-Positive Macrophages in Idiopathic Interstitial Pneumonias - Masahiro Yamashita; Ryoko Saito; Shinji Yasuhira; Yuh Fukuda; Hironobu Sasamo; Tamotsu Sugai; Kohei Yamauchi; Makoto Maemondo (Journal of Immunology Research)
Background. The types of cells most significantly linked to individual subtypes of idiopathic interstitial pneumonias (IIPs) remain unclear. Few studies have examined CD163+ macrophages in IIPs. Objective. We retrospectively aimed to immunohistochemically characterize the CD163+ macrophages in IIPs. Methods. Paraffin-embedded lung tissue samples were obtained from 47 patients with IIPs, including idiopathic pulmonary fibrosis (IPF), idiopathic nonspecific interstitial pneumonia (NSIP), and cryptogenic organizing pneumonia (COP), and 12 normal controls were immunohistochemically analyzed, using primary antibodies against CD68 and CD163 as indicators of pan and M2 macrophages, respectively. Results. CD68+ macrophage density was significantly increased in the 3 subtypes of IIPs relative to that in the control group, although no difference was detected within the different IIPs. CD163+ macrophage density was significantly increased in NSIP and COP samples relative to that in IPF samples. The density ratio of CD163+ macrophages to CD68+ macrophages was significantly decreased in IPF/UIP samples relative to that in the others, while the densities in NSIP and COP were significantly higher than those in control cases. Conclusion. CD163+ macrophages show distinct profiles among IIPs, and the standardized numerical density is decreased in IPF cases that have poor prognoses.